2008
DOI: 10.3324/haematol.13855
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic nucleophosmin is not detected in blastic plasmacytoid dendritic cell neoplasm

Abstract: the presence of NPM1 mutations) but nucleus-restricted in BPDC neoplasm (because of a germline NPM1 gene). Our results, have important diagnostic implications, further clarify the cell of origin of NPMc + AML, and justify the inclusion of AML with mutated NPM1 and BPDC neoplasm as separate entities in the new WHO classification. Design and Methods Pathological samplesThe aim of this study was to investigate the presence of NPM1 mutations in a wide spectrum of PDC proliferations. The following pathological samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 20 publications
(25 reference statements)
1
22
0
Order By: Relevance
“…13,23,24 In our series cytogenetic analysis confirmed that most patients had unfavorable cytogenetics (48%), among which complex karyotype was a distinctive feature. Moreover, as recently found, 25 no patients had NPM1 mutations. Of interest, among 14 cases examined in our series, three had FLT3-ITD mutations.…”
Section: Discussionsupporting
confidence: 64%
“…13,23,24 In our series cytogenetic analysis confirmed that most patients had unfavorable cytogenetics (48%), among which complex karyotype was a distinctive feature. Moreover, as recently found, 25 no patients had NPM1 mutations. Of interest, among 14 cases examined in our series, three had FLT3-ITD mutations.…”
Section: Discussionsupporting
confidence: 64%
“…9,10 BPDCN affects predominantly elderly males, with the median age of affected patients reported to be in the sixth decade. [11][12][13] It is characterized by the simultaneous occurrence of cutaneous and extracutaneous (bone marrow, lymph node, and peripheral blood) involvement. [14][15][16] Cutaneous involvement (either in the form of isolated purple nodules or macules or disseminated lesions) is estimated to occur in 85% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…As pictured in Figure 1C, chromatin is typically dispersed, and nuclear membranes are irregular with prominent nucleoli and increased mitotic activity. [17][18][19] The clinical and histologic presentation are most similar to myelomonocytic (M4) or monoblastic/monocytic (M5) leukemia with skin involvement, typically referred to as LC, aleukemic myeloperoxidase LC (MPO-LC), 17,20 or more rarely CD4…”
Section: Morphologymentioning
confidence: 99%
“…21,22 Thus, multiple recent case reports have further defined both immunophenotypic and cytogenetic profiles by which to differentiate BPDCN from other similar appearing myeloid-derived malignancies. 10,17,20,23 Immunophenotype Figure 1D shows the shared and unique immunohistochemical markers that allow BPDCN to be accurately differentiated from AML or AML-associated LC or myeloid sarcoma. For BPDCN originating as isolated cutaneous lesions without organ involvement, immunohistochemistry is of particular importance, because biopsy specimens may not yield sufficient cells for differentiation via flow cytometric analysis.…”
Section: Cd56mentioning
confidence: 99%